2005
DOI: 10.1073/pnas.0504014102
|View full text |Cite
|
Sign up to set email alerts
|

Partner-regulated interaction of IFN regulatory factor 8 with chromatin visualized in live macrophages

Abstract: IFN regulatory factor (IRF) 8 is a transcription factor that directs macrophage differentiation. By fluorescence recovery after photobleaching, we visualized the movement of IRF8-GFP in differentiating macrophages. Recovery data fitted to mathematical models revealed two binding states for IRF8. The majority of IRF8 was highly mobile and transiently interacted with chromatin, whereas a small fraction of IRF8 bound to chromatin more stably. IRF8 mutants that did not stimulate macrophage differentiation showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 39 publications
4
43
0
Order By: Relevance
“…It has been well shown that IFN-g binding to its receptor triggers signal transducers and activators of transcription 1 (STAT1) phosphorylation and dimerization. The dimerized STAT1 then translocates to the nucleus and binds directly to the IRF8 promoter element (the GAS element) to activate IRF8 transcription (37,38,48). Because IFN-g up-regulates Fas expression in SW620 cells, it is reasonable to assume that the function of STAT1 in the IFN-g receptor-initiated signaling pathway is not altered.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well shown that IFN-g binding to its receptor triggers signal transducers and activators of transcription 1 (STAT1) phosphorylation and dimerization. The dimerized STAT1 then translocates to the nucleus and binds directly to the IRF8 promoter element (the GAS element) to activate IRF8 transcription (37,38,48). Because IFN-g up-regulates Fas expression in SW620 cells, it is reasonable to assume that the function of STAT1 in the IFN-g receptor-initiated signaling pathway is not altered.…”
Section: Discussionmentioning
confidence: 99%
“…4e-g), which is consistent with the results in 293T cells. Of note, neither IRF8 K79E nor IRF8 R289E induces monocyte differentiation-related IRF8 target genes 22,29 , suggesting that the modes of IRF8 action in promoting monocyte differentiation and inhibiting neutrophil differentiation are indeed distinct.…”
Section: Genes Upregulated By C/ebpαmentioning
confidence: 99%
“…IRF8 K79E is defective in DNA binding, while IRF8 R289E cannot interact with PU.1 and other IRFs 28 . Neither mutant is capable of inducing macrophage and DC differentiation 10,28,29 . Interestingly, IRF8 R289E still blocked the transactivation by C/EBPa, whereas IRF8 K79E lost this inhibitory effect, suggesting the involvement of DBD in the inhibition of C/EBPa activity.…”
Section: Irf8 Protein Expression In Myeloid Progenitor Populationsmentioning
confidence: 99%
“…Mass spectrometry was performed in the Proteomics and Mass Spectrometry Facility of National Institute of Diabetes and Digestive and Kidney Diseases, National Institutes of Health. GST pull-down assays and bifluorescence complementation analysis were performed as described (18,19).…”
Section: Purification Of Irf-8 Immune Complex and Interaction Assaysmentioning
confidence: 99%